2016
DOI: 10.2119/molmed.2015.00136
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-15a/16 Regulates Apoptosis of Lung Epithelial Cells After Oxidative Stress

Abstract: Lung epithelial cell apoptosis is an important feature of hyperoxia-induced lung injury. The death receptor-associated extrinsic pathway and mitochondria-associated intrinsic pathway both mediate the development of lung epithelial cell apoptosis. Despite decades of research, molecular mechanisms of hyperoxia-induced epithelial cell apoptosis remain incompletely understood. Here, we report a novel regulatory paradigm in response to hyperoxia-associated oxidative stress. Hyperoxia markedly upregulated microRNA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Assessment of the genes targeted by miR-23a-3p, miR-15a-5p, miR-223-3p, and miR-1285-3p involved in the mucin-type O-glycan biosynthetic signaling pathway predicted representatively the MET proto-oncogene (MET), epidermal growth factor receptor (EGFR), beta-actin (ACTB), transforming growth factor beta receptor (TGF-βR), and poly(ADP-ribose) polymerase 1 (PARP1). The previous studies shown in Table 3 showed each miRNA’s role in disease progression, fibrosis, and inflammation, which was consistent with our results with regard to inflammatory diseases, but opposite results were also confirmed in some references denoted with asterisks [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Resultssupporting
confidence: 93%
“…Assessment of the genes targeted by miR-23a-3p, miR-15a-5p, miR-223-3p, and miR-1285-3p involved in the mucin-type O-glycan biosynthetic signaling pathway predicted representatively the MET proto-oncogene (MET), epidermal growth factor receptor (EGFR), beta-actin (ACTB), transforming growth factor beta receptor (TGF-βR), and poly(ADP-ribose) polymerase 1 (PARP1). The previous studies shown in Table 3 showed each miRNA’s role in disease progression, fibrosis, and inflammation, which was consistent with our results with regard to inflammatory diseases, but opposite results were also confirmed in some references denoted with asterisks [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Resultssupporting
confidence: 93%
“…All animal experiments were performed in accordance with the approved guidelines. For normoxia and hyperoxia conditions, mice were exposed to room air and hyperoxia (100% oxygen), respectively, as previously described ( Cao et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“… 28 Overexpression of miR-23a∼27a∼24-2 cluster increased ROS production and induced caspase-dependent and -independent apoptosis in human embryonic kidney cells. 29 Cao et al 30 reported that miR-15a/16 deficiency resulted in lung epithelial cell apoptosis in response to hyperoxia, by modulating both intrinsic and extrinsic apoptosis.…”
Section: Discussionmentioning
confidence: 99%